Legal protection of internal doctors medical services in the city of Makassar - Fajrin Amin (Requisitoire Law Enforcement, 2022)
In discussing this thesis, the author uses a normative legal research approach. The data sources for this research come from primary legal materials, secondary legal materials, and tertiary legal materials. This research is classified as qualitative, using data in the form of direct interviews/questions and answers (dialogue) and documentation studies. The results of this study indicate that legal protection for doctors really needs to be done with various factors that cause it either caused by the behavior of the patient himself or the natural nature of a doctor in general, even though for the city of Makassar itself it turns out that there have been no cases that have reached court related to the actual alleged malpractice which has its own criteria to be considered as an act of malpractice, The main step taken to protect doctors from being dragged to court is by trying to resolve a problem through mediation, which is also a mandate from the health law. The implications of the results of this study are that in the future doctors should be able to understand more about legal responsibility because it will be very helpful in anticipating possible patient demands for medical efforts made by doctors.